2018
DOI: 10.1038/s41598-018-24715-2
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the phytoremediation efficiency of Neyraudia reynaudiana for lead-zinc mine-contaminated soil under the interactive effect of earthworms and EDTA

Abstract: Slow plant growth, low biomass, and low bioavailability of heavy metals in soil are important factors that limit remediation efficiencies. This study adopted a pot cultivation method to evaluate the phytoremediation efficiency of Neyraudia reynaudiana, planted in contaminated soil from a lead-zinc mining area. The soil was inoculated with earthworms (Eisenia fetida), and mixed with the chelating agent ethylenediaminetetraacetic acid (EDTA) one month after planting. The addition of earthworms significantly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Regarding Cu concentration and content in plants, Fe-EDTA was significantly more effective than Fe-EDDHA. EDTA was shown to have a high binding constant for Cu, allowing its dissolution (Li et al 2018). Ghasemi-Fasaei et al (2005) reported that soil application of Fe-EDTA increased the content and concentration of Cu in chickpea significantly, whereas Abo-Rady et al (1987) found soil application of Fe-EDDHA had no significant effect on Cu concentration in the leaves of two different date varieties.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Cu concentration and content in plants, Fe-EDTA was significantly more effective than Fe-EDDHA. EDTA was shown to have a high binding constant for Cu, allowing its dissolution (Li et al 2018). Ghasemi-Fasaei et al (2005) reported that soil application of Fe-EDTA increased the content and concentration of Cu in chickpea significantly, whereas Abo-Rady et al (1987) found soil application of Fe-EDDHA had no significant effect on Cu concentration in the leaves of two different date varieties.…”
Section: Discussionmentioning
confidence: 99%
“…2a). Li et al (2018) showed that after EDTA application, , the exchangeable Pb fraction increased significantly (17-90%) whereas the residual Pb fraction decreased (10-23%) suggesting that the complexation of EDTA and Pb is facilitated by Pb conversion from the residual fractions to exchangeable fractions, which then increased plant availability. In fact, the overall changes (sum of changes) in the Pb fractions (Exch, Carb, Oxide and Org) was around ±12.1% indicating mobilization/immobilization for a proportion of the residual Pb fraction but with no clear trend.…”
Section: Chelate Induced Redistribution Of Metal Fractions In Iw Treamentioning
confidence: 99%
“…Naturally occurring species such as aromatic plants and energy crops can grow in such contaminated sites that accumulate heavy metals very well. In order to enhance the metal uptake by plants, strategies such as the addition of chelating agents such as ethylenediaminetetraacetic acid (EDTA), ethylenediamine-N, N'-disuccinic acid (EDDS), humic substances have been successful (Luo et al, 2018).…”
Section: Enhancing the Bioavailability Of Metals For Uptake By Plantsmentioning
confidence: 99%